Exploring global and local patterns in the correlation of geographic distances and morphosyntactic variation in Swiss German. Issue 2 (12th December 2017) - Jeszenszky, Péter; Stoeckle, Philipp; Glaser, Elvira; Weibel, Robert
Abstract : Using data from a Swiss German dialect syntax survey, this study aims to explore, in a spatially differentiated manner, the correlation between dialectal variation and geographic distances. A linguistic distance was expressed by a measure aggregated from 60 survey questions. To operationalize the possibility of language contact, Euclidean distance, as well as travel times in 2000, 1950 and 1850 between survey sites were used. Going beyond previous work by others, we also explore the covariation of geographic and linguistic distances at the local level, focusing on spatial subsets and individual survey sites, thus being able to paint a more differentiated picture. With the diverse physical landscape of Switzerland making an impact on potential language contact, we find that travel times are a better predictor than Euclidean distance for the syntactic variation in Swiss German dialects. However, on the local scale the difference is not always significant, depending on prevalent topography.